Recruiting with Social Media: Social Media's Impact on Recruitment and HR - Raj Anand (Que, 2010)
The power of recruiting people with Social Media! Social Media is not only an effective marketing tool to get candidates and customers onboard but also a tool to help decrease costs on communication, interaction, knowledge management/transfer inside a company and externally with suppliers and customers.